Exploration of highly accelerated magnetic resonance elastography using high-density array coils - Bosshard, John C.; Yallapragada, Naresh; McDougall, Mary P.; Wright, Steven M. (Quantitative Imaging in Medicine and Surgery, 2017)
Background: Magnetic resonance elastography (MRE) measures tissue mechanical properties by applying a shear wave and capturing its propagation using magnetic resonance imaging (MRI). By using high density array coils, MRE images are acquired using single echo acquisition (SEA) and at high resolutions with significantly reduced scan times. Methods: Sixty-four channel uniplanar and 32×32 channel biplanar receive arrays are used to acquire MRE wave image sets from agar samples containing regions of varying stiffness. A mechanical actuator triggered by a stepped delay time introduces vibrations into the sample while a motion sensitizing gradient encodes micrometer displacements into the phase. SEA imaging is used to acquire each temporal offset in a single echo, while multiple echoes from the same array are employed for highly accelerated imaging at high resolutions. Additionally, stiffness variations as a function of temperature are studied by using a localized heat source above the sample. A custom insertable gradient coil is employed for phase compensation of SEA imaging with the biplanar array to allow imaging of multiple slices. Results: SEA MRE images show a mechanical shear wave propagating into and across agar samples. A set of 720 images was obtained in 720 echoes, plus a single reference scan for both harmonic and transient MRE. A set of 2,950 wave image frames was acquired from pairs of SEA images captured during heating, showing the change in mechanical wavelength with the change in agar properties. A set of 240 frames was acquired from two slices simultaneously using the biplanar array, with phase images processed into displacement maps. Combining the narrow sensitivity patterns and SNR advantage of the SEA array coil geometry allowed acquisition of a data set with a resolution of 156 µm × 125 µm × 1,000 µm in only 64 echoes, demonstrating high resolution and high acceleration factors. Conclusions: MRE using high-density arrays offers the unique ability to acquire a single frame of a propagating mechanical vibration with each echo, which may be helpful in non-repeatable or destructive testing. Highly accelerated, high resolution MRE may be enabled by the use of large arrays of coils such as used for SEA, but at lower acceleration rates supporting the higher resolution than provided by SEA imaging.